Compósitos de gelatina-hidroxiapatita contendo doxiciclina obtidos por abordagem biomimética, com potencial osteogênico e prospecção tecnológica - Sandra Daniela Motta Rodríguez (2022)
Worldwide, the prevalence of disorders and bone diseases has shown an increased and intensified trend, with approximately 2 million bone graft procedures performed per year. Artificially developed bone tissue has been seen as a potential alternative to the conventional use of bone grafts. Due to their unlimited supply and non-transmission of diseases, biopolymers are becoming increasingly popular for various biomedical applications due to their many advantages, including cytocompatibility and non-toxic degradation. Most polymeric materials that contribute to the development of scaffolds generally do not provide the desired mechanical and degradation properties for the matrix because they have few bonds between the polymer chains, whereby crosslinking is a simple method in which chemical or physical bonds are established between polymeric chains to modify the mechanical, biological and degradation properties of polymeric materials. In this scenario, the purpose of Chapter 1 is to analyze the use of scaffolds or biomedical composites from hydrogels to release drugs used in the replacement of biological tissues at the technological frontiers based on a bibliometric analysis from the state of the art with Scopus and Web of Science databases, starting with an annual categorization of the articles obtained in each database, followed by an analysis of the most productive countries/regions with their citations, continuing with a distribution of the most cited journals and articles and ending with a mapping and analysis of the co occurrence of the main keywords obtained in each article, and a patentometry based on the state of the art with the Lens.org and Orbit Intellligende da Questel databases and the IPC code A61K9/00. Data were obtained to analyze the panorama of the most productive countries/regions and institutions, categorical analysis, legality, the countries that protect technologies in Brazil, and an analysis focused on the evolution of innovation in Brazil in recent years. In Chapter 2, two hybrid polymeric scaffolds of gelatin – hydroxyapatite (HA) with 1 and 5% / were created, crosslinked with 0.7% / of EDC and doxycycline concentrations of 0.3, 0.7, and 1.2% / were developed. Porosity, Fourier transform infrared absorption spectroscopy (FT-IR), X-ray diffraction (XRD), thermogravimetry (TG/DTG), and scanning electron microscopy (SEM) were used to analyze them. The behavior of pH, swelling capacity, degradation, and enzymatic degradation, the doxycycline release profile, the influence of crosslinker on scaffolding, and the minimum inhibitory concentration (MIC) of doxycycline against S. aureus were assessed. At the end on the scaffolds, indirect viability tests were performed on fibroblasts (L919), and pre osteoblasts (MC3T3). And an adhesion and proliferation test were made on pre osteoblasts (MC3T3) cells. The results indicated that the scaffold composed of 1% / lyophilized hydrogel, 0.7% / EDC crosslinker, and 0.3% / doxycycline improved pre-osteoblastic cell proliferation, with drug release profiles and steady enzymatic biodegradation consistent with bone regeneration time.